Defect engineering of oxygen vacancies in SnOx electron transporting layer for perovskite solar cells. (June 2019) - Jiang, Ershuai; Yan, Jin; Ai, Yuqian; Li, Nan; Yan, Baojie; Zeng, Yuheng; Sheng, Jiang; Ye, Jichun
Abstract: In this work, we present the self-passivation of tin oxide (SnOx ) electron transporting layer (ETL) induced by manipulatively filling the oxygen vacancies for perovskite solar cells (PSCs). The oxygen component of SnOx ETL is tuned by the annealing under the oxygen (O2 ) atmosphere to control the trap state density for high electron collection efficiency. With increasing the O2 content when annealing, oxygen vacancies of SnOx ETL are filled gradually, with the x of SnOx being up to 1.84, while the crystalline structure grown better to be rutile. Furthermore, the measurement of electron transport dynamic demonstrates that the SnOx ETL is benefit for electron collection after O2 -annealed, and receiving high power conversion efficiency (PCE) of PSCs. The PSC based on the O2 -annealed SnOx ETL yields an average PCE of over 19%, much higher than 17.81% of that after N2 -annealing. The O2 -annealed PSC gives a champion PCE of 20.40%, with a short current density of 24.41 mAcm −2, an open circuit voltage of 1.14 V and a fill factor of 73.37%. Therefore, the annealing is an efficient and simple way to control the quality of SnOx ETL for the high performance PSCs. Graphical abstract: The oxygen vacancy density of the SnOx electron transporting layer (ETL) for perovskite solar cell (PSC) is controlled by annealing in the different O2 /N2 gas flow, aiming to improve the carrier collection efficiency. After annealing under the O2 atmosphere, the SnOx -based PSC receives the high power conversion efficiency of 20.41%, due to the increased electron mobility and reduced trap-state density of ETL.Image 1 Highlights: Charge carrier collection efficiency of metal oxide dominated by the trap-state density. Oxygen vacancy of SnOx film filled by the oxygen atoms during the O2 annealing. Improved electron transporting layer based on the better crystalline structure and less defect. 20.40% power conversion efficiency of SnOx -based perovskite solar cell.